What to make of cannabis and cognition in MS: In search of clarity amidst the haze. (December 2015) - Feinstein, Anthony; Banwell, Emma; Pavisian, Bennis
Given data showing that cannabis (herbal drug from the Cannabis sativa plant) can impair cognition in healthy subjects, the possibility that it may also do so in people with multiple sclerosis (MS) should be cause for concern. Approximately 20% of people with MS inhale or ingest cannabis for a variety of symptoms, or as a lifestyle choice. In addition, pharmaceutically manufactured cannabis (in capsules or spray) is prescribed most often for pain and spasticity; however, there is a dearth of literature on the cognitive effects of cannabis. Furthermore, methodological limitations introduce a cautionary note when interpreting the data. The evidence, which must therefore be considered preliminary, suggests that smoked cannabis may further compromise information processing speed and memory, with magnetic resonance imaging (fMRI) demonstrating more inefficient patterns of cerebral activation during task performance. The findings related to pharmaceutically manufactured cannabis are equivocal. There is a pressing need for further research to inform clinical opinion, which at present reflects a combination of uncertainty and dogma.